The Effect Of Recruitment, Training, And Compensation On Employee Performance At Bank Bengkulu - Nirman Azhari; Sulisti Afriani; Lydia Gustina Putri (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
This research is motivated by the importance of human resource management in improving organizational performance, especially in the highly competitive banking sector. Bank Bengkulu as a regional financial institution is required to be able to optimize the performance of its employees through a selective recruitment process, relevant training, and a fair and motivating compensation system. These three aspects have a strategic role in creating a quality, productive, and loyal workforce to the organization. The objective of this study is to determine the influence of recruitment, training, and compensation both partially and simultaneously on the performance of Bank Bengkulu employees. The method used is a quantitative approach by distributing questionnaires to 30 respondents who are permanent employees of Bank Bengkulu. The data was analyzed using validity tests, reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) with the help of the SPSS version 26 program to test the hypotheses that had been formulated. The results showed that recruitment has a positive and significant effect on employee performance, training has a negative and significant effect, while compensation has a positive but not significant effect on employee performance. Simultaneously, these three variables have a significant effect on performance with an F count of 12.834 and an R² of 0.733, which means that 73.3% of the variation in employee performance is explained by these three variables.